Vanuatu Psychiatry Mentorship Programme: a case illustrating cultural and clinical considerations. (February 2020) - Obed, Jimmy; Bush, Allister; Stathis, Stephen; Hunter, Ernest
Objectives: The objectives of this article are to describe a case highlighting challenges in managing an acute psychiatric presentation, the process of mentorship and the significance of cultural matters influencing family engagement in Vanuatu. Method: Case description. Results: This case highlights resourcing constraints facing a small mental health team in the Pacific, the clinical significance of the concept of tabu in a ni-Vanuatu context and the importance of family decision making processes in ni-Vanuatu culture. Conclusion: A structured mentoring programme to foster mental health capacity development in Vanuatu can support psychiatric decision-making in complex cases, reflection on the role of culture in formulation and family engagement, and mutual learning.